2021
DOI: 10.3847/1538-4357/ac0ef2
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Powerful Outflows Detected in High-z Quasars

Abstract: We present results from a comprehensive study of ultrafast outflows (UFOs) detected in a sample of 14 quasars, 12 of which are gravitationally lensed, in a redshift range of 1.41-3.91, near the peak of the active galactic nucleus (AGN) and star formation activity. New XMM-Newton observations are presented for six of them, which were selected to be lensed and contain a narrow absorption line (NAL) in their UV spectra. Another lensed quasar was added to the sample, albeit already studied because it was not searc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 106 publications
1
34
0
Order By: Relevance
“…This scaling is significantly different from the one often assumed in models of AGN feedback used in cosmological simulations of galaxy formation, where the energy injection rate is assumed to be proportional to the mass accretion rate and hence to the bolometric luminosity (Schaye et al 2015;Weinberger et al 2017;Davé et al 2019). However, it is consistent with the results found in the hydrodynamical simulations of Nomura & Ohsuga (2017) and with current observational constraints (Gofford et al 2015;Chartas et al 2021).…”
Section: Dependence On Bh Mass and Mass Accretion Ratesupporting
confidence: 92%
“…This scaling is significantly different from the one often assumed in models of AGN feedback used in cosmological simulations of galaxy formation, where the energy injection rate is assumed to be proportional to the mass accretion rate and hence to the bolometric luminosity (Schaye et al 2015;Weinberger et al 2017;Davé et al 2019). However, it is consistent with the results found in the hydrodynamical simulations of Nomura & Ohsuga (2017) and with current observational constraints (Gofford et al 2015;Chartas et al 2021).…”
Section: Dependence On Bh Mass and Mass Accretion Ratesupporting
confidence: 92%
“…More recently, on 2016 January 13, SDSS J1353+1138 was observed with XMM-Newton . The analysis of the X-ray spectrum (Chartas et al 2021) revealed a significant absorption at ∼ 6.8 keV (consistent with Fe XXV), indicating the presence of a ∼ 0.31c UFO.…”
Section: Sdss J1353+1138mentioning
confidence: 64%
“…Our sample consists of two z ∼ 1.5 multiple lensed QSOs, HS 0810+2554 and SDSS J1353+1138, observed with the Spectrograph for INtegral Field Observations in the Near Infrared (SINFONI, Eisenhauer et al 2003) at the ESO Very Large Telescope (VLT) Unit Telescope 3 (UT3) within the framework of the program 0102.B-0377(A) (PI: G. Cresci). These objects were specifically selected as they are known to host UFOs (Chartas et al 2016;Chartas et al 2021) and to be at redshifts (z ∼ 1.5 and z ∼ 1.6 for HS 0810+2554 and SDSS J1353+1138, respectively), such that the optical rest-frame emission (tracing ionised outflows) falls in the range of wavelengths observed by SIN-FONI, namely, in the near-IR J-band (λ ∼ 1.1 − 1.4 µm). Consequently, this selection in redshifts corresponds to study objects at epochs close to the peak of AGN activity (z ∼ 2).…”
Section: Selection Of Targetsmentioning
confidence: 99%
See 2 more Smart Citations